Community awareness and experiences of health workers concerning mosquito-borne viral diseases in selected districts of Gambella Region, Southwestern Ethiopia. Issue 1 (1st January 2021) - Asebe, Getahun; Mamo, Gezahegne; Wieland, Barbara; Medhin, Girmay; Tilahun, Getachew; Abegaz, Woldaregay Erku; Legesse, Mengistu
ABSTRACT: In this study, we assessed community awareness and experiences of health workers about mosquito-borne viral diseases in selected districts of the Gambella Region, South Western Ethiopia. A community and health facility-based qualitative study involving 11 focus group discussions (FGDs) with community dmembers and two FGDs with health workers was conducted between November 2017 to January 2018. A total of 122 community members and 16 health workers participated in the study. All the discussants mentioned malaria, typhoid fever, unknown causes of diarrhea and skin diseases as the major public health problems in the area. Using pictures of Anopheles and Aedes mosquitoes, participants confirmed that both mosquitoes are present in the area. They identified Anopheles as the vector of malaria. However, community discussants could not mention the name of a disease that can be transmitted by Aedes mosquito though they mentioned that Aedes mosquito bites both humans and animals during the day time in forest areas and causes skin itching to humans. Meanwhile, community participants from Pakag, a village bordering South Sudan, expressed concern that Aedes mosquito can cause a malaria-like disease which can kill within a few days. Health workers from Itang health center described that in 2016, an outbreak of an unknown disease that causes fever and jaundice occurred and killed seven individuals in a village called Akula, which is closer to a South Sudan refugee camp. Overall, the findings showed that community members and health workers in the area do not have adequate information on mosquito-borne viral diseases. Creating awareness, improving laboratory services and further epidemiological studies would be important for early warning and preparedness for outbreaks in the area.